2014
DOI: 10.1002/jwmg.776
|View full text |Cite
|
Sign up to set email alerts
|

Post-parturition habitat selection by elk calves and adult female elk in New Mexico

Abstract: Neonatal survival and juvenile recruitment are crucial to maintaining viable elk (Cervus elaphus) populations. Neonate survival is known to be influenced by many factors, including bed‐site selection. Although neonates select the actual bed‐site location, they must do so within the larger calf‐rearing area selected by the mother. As calves age, habitat selection should change to meet the changing needs of the growing calf. Our main objectives were to characterize habitat selection at 2 spatial scales and in ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 48 publications
(83 reference statements)
3
34
1
Order By: Relevance
“…Similarly, Festa‐Bianchet and Côté () reported that only 30% of parturition sites of mountain goats ( Oreamnos americanus ) were on cliffs, the majority were in areas with more gentle terrain that were seldom used by mountain goats during other times of year. Analogous findings have been reported for elk (Rearden et al , Pitman et al ), pronghorn (Canon and Bryant ), and white‐tailed deer ( Odocoileus virginianus ; Huegel et al ).…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, Festa‐Bianchet and Côté () reported that only 30% of parturition sites of mountain goats ( Oreamnos americanus ) were on cliffs, the majority were in areas with more gentle terrain that were seldom used by mountain goats during other times of year. Analogous findings have been reported for elk (Rearden et al , Pitman et al ), pronghorn (Canon and Bryant ), and white‐tailed deer ( Odocoileus virginianus ; Huegel et al ).…”
Section: Discussionsupporting
confidence: 80%
“…Moose and red deer ( Cervus elaphus ) have been observed seeking out high quality forage during lactation (Clutton‐Brock et al , Melin et al ). However, other ungulates typically continue to avoid predation at the expense of access to forage while juveniles are at‐heel (Pitman et al , Smith et al , Karsch et al ). Restricted access to forage during lactation in white‐tailed deer has resulted in fawns gaining less mass, nursing more, and spending more time with their mothers foraging, and in survival decreasing 35% (Therrien et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…) and to fulfill their shifting resource requirements (e.g., elk selecting birthing sites in the spring; Pitman et al. ), greater consistency in resource availability or an increase in fine‐scale resource needs at a particular scale may dampen or intensify the relevance of any given scale. For instance in our study, model‐averaged coefficients indicated that elk diel preference for individual habitat variables varied seasonally, but model selection indicated that changes in elk diel preferences were less pronounced in winter and summer than in spring and fall.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal shifts in behavior can indicate the temporal scale of spawning or parturition periods (Pitman et al. ), and diel shifts in behavior can indicate changes between foraging and resting areas with sufficient cover to avoid predators (Holomuzki , Creel et al. , Robinson et al.…”
Section: Introductionmentioning
confidence: 99%